Trypanosoma cruzi 80 kDa prolyl oligopeptidase (Tc80) as a novel immunogen for Chagas disease vaccine. - Augusto E Bivona; Andrés Sánchez Alberti; Marina N Matos; Natacha Cerny; Alejandro C Cardoso; Celina Morales; Germán González; Silvia I Cazorla; Emilio L Malchiodi (Public Library of Science (PLoS), 2018)
BACKGROUND:Chagas disease, also known as American Trypanosomiasis, is a chronic parasitic disease caused by the flagellated protozoan Trypanosoma cruzi that affects about 8 million people around the world where more than 25 million are at risk of contracting the infection. Despite of being endemic on 21 Latin-American countries, Chagas disease has become a global concern due to migratory movements. Unfortunately, available drugs for the treatment have several limitations and they are generally administered during the chronic phase of the infection, when its efficacy is considered controversial. Thus, prophylactic and/or therapeutic vaccines are emerging as interesting control alternatives. In this work, we proposed Trypanosoma cruzi 80 kDa prolyl oligopeptidase (Tc80) as a new antigen for vaccine development against Chagas disease. METHODOLOGY/PRINCIPAL FINDINGS:In a murine model, we analyzed the immune response triggered by different immunization protocols based on Tc80 and evaluated their ability to confer protection against a challenge with the parasite. Immunized mice developed Tc80-specific antibodies which were able to carry out different functions such as: enzymatic inhibition, neutralization of parasite infection and complement-mediated lysis of trypomastigotes. Furthermore, vaccinated mice elicited strong cell-mediated immunity. Spleen cells from immunized mice proliferated and secreted Th1 cytokines (IL-2, IFN-γ and TNF-α) upon re-stimulation with rTc80. Moreover, we found Tc80-specific polyfunctional CD4 T cells, and cytotoxic T lymphocyte activity against one Tc80 MHC-I peptide. Immunization protocols conferred protection against a T. cruzi lethal challenge. Immunized groups showed a decreased parasitemia and higher survival rate compared with non-immunized control mice. Moreover, during the chronic phase of the infection, immunized mice presented: lower levels of myopathy-linked enzymes, parasite burden, electrocardiographic disorders and inflammatory cells. CONCLUSIONS/SIGNIFICANCE:Considering that an early control of parasite burden and tissue damage might contribute to avoid the progression towards symptomatic forms of chronic Chagas disease, the efficacy of Tc80-based vaccines make this molecule a promising immunogen for a mono or multicomponent vaccine against T. cruzi infection.